Die goedkeuring van kerkrade vir 'n nuwe verband in die NG Kerkfamilie? - PJ Strauss (Acta Theologica)
This article probes the question of which assembly within a reformed church denomination - in this case the family of Dutch Reformed Churches - should have the jurisdiction in deciding on the alteration of the confession(s) and especially, the constitution and contents of this denomination. The conclusion is a fairly simple one. If it is accepted that che congregation, as governed by consistories, is a fully fledged church and that congregations constitute a specific denomination, then the consistories involved should decide the matter. Congregations should be able to give their consent co the new denomination they enter into. On che one hand the undefined and general structural unity of rhe church, is a Biblical principle. On the ocher hand, the formulation and constitution of confessions and specific denominations is a matter for the believers within a certain historical concext. They should also be able to enter into a structure of church unity willingly and in the belief - because the church is an institution of faith - that it is the will of God.